Identification of CD34+/PGDFRα+ Valve Interstitial Cells (VICs) in Human Aortic Valves: Association of Their Abundance, Morphology and Spatial Organization with Early Calcific Remodeling - Grzegorz J. Lis (International Journal of Molecular Sciences, 2020)
Aortic valve interstitial cells (VICs) constitute a heterogeneous population involved in the maintenance of unique valvular architecture, ensuring proper hemodynamic function but also engaged in valve degeneration. Recently, cells similar to telocytes/interstitial Cajal-like cells described in various organs were found in heart valves. The aim of this study was to examine the density, distribution, and spatial organization of a VIC subset co-expressing CD34 and PDGFRα in normal aortic valves and to investigate if these cells are associated with the occurrence of early signs of valve calcific remodeling. We examined 28 human aortic valves obtained upon autopsy. General valve morphology and the early signs of degeneration were assessed histochemically. The studied VICs were identified by immunofluorescence (CD34, PDGFRα, vimentin), and their number in standardized parts and layers of the valves was evaluated. In order to show the complex three-dimensional structure of CD34+/PDGFRα+ VICs, whole-mount specimens were imaged by confocal microscopy, and subsequently rendered using the Imaris (Bitplane AG, Zürich, Switzerland) software. CD34+/PDGFRα+ VICs were found in all examined valves, showing significant differences in the number, distribution within valve tissue, spatial organization, and morphology (spherical/oval without projections; numerous short projections; long, branching, occasionally moniliform projections). Such a complex morphology was associated with the younger age of the subjects, and these VICs were more frequent in the spongiosa layer of the valve. Both the number and percentage of CD34+/PDGFRα+ VICs were inversely correlated with the age of the subjects. Valves with histochemical signs of early calcification contained a lower number of CD34+/PDGFRα+ cells. They were less numerous in proximal parts of the cusps, i.e., areas prone to calcification. The results suggest that normal aortic valves contain a subpopulation of CD34+/PDGFRα+ VICs, which might be involved in the maintenance of local microenvironment resisting to pathologic remodeling. Their reduced number in older age could limit the self-regenerative properties of the valve stroma.